WETLAND HYDROLOGY AND HYDRAULICS: WATER QUALITY ASSESSMENT - M. E. Grismer (Lowland Technology International, 1999)
Wetlands function in the transitional environment between terrestrial and aquatic ecosystems and their impact on water quality enhancement (as well as biological diversity) is directly dependent on the hydrologic, or hydraulic factors controlling the residence, or detention time of the water within the wetland. Similarly, constructed wetland performance, in terms of wastewater treatment efficiency, also depends on the processes affecting water detention within the system. In many cases, however, both the hydrologic, or hydraulic factors and the actual degradation processes or mechanisms associated with particular constituents of concern are only poorly understood. Successful wetland restoration, or design of constructed wetlands for wastewater treatment requires a thorough understanding of the site hydrology, or flow hydraulics as well as an assessment of the specific constituent degradation mechanisms of concern. In this paper, some of the current literature associated with development of the concepts outlined above is reviewed. Examples of how these concepts may apply to a range of wetland types are considered; including a sub-alpine bog/fen, a tidal marsh, and constructed surface and subsurface flow wetlands.